In situ off‐line extracorporeal photopheresis conducted in a real‐life situation at a Hemobiotherapy Department in France: A comparison of costs vs on‐line procedure. Issue 1 (2nd November 2021) - Azar, Nabih; Ouzegdouh, Maya; Choquet, Sylvain; Goncalves, Natalia; Leblond, Véronique
Abstract: Background: The off‐line extracorporeal photopheresis (ECP) procedure requires photosensitization in an external cell therapy laboratory as per the French regulatory requirement. This regulation results in higher time and costs compared with the on‐line alternative performed entirely at the patient's bedside. Recently, full in situ execution of the off‐line procedure has been implemented in the Pitié‐Salpêtrière Hospital Hemobiotherapy Department (Paris, France). This report summarizes the center's experience regarding the organizational and costs impacts of this change compared with the on‐line procedure. Material and methods: ECP was broken down into stages, and several procedures were monitored prospectively in real‐life settings. The total costs associated with both procedures were the sum of the fixed costs and variable costs related to all stages of the procedures, nursing‐time costs, property costs, and patient‐related production loss costs. Results: Eight off‐line ECP and fourteen on‐line ECP procedures were monitored during five consecutive days. Procedure duration was not different (median 137.5 vs 154.0 minutes, P = .29). Times and costs associated with nursing were higher but offset by lower fixed costs of the off‐line ECP. Total direct costs per procedure associated with using the off‐line ECP were significantly lower than those of the on‐line procedure (459.6 ± 7.1 EUR vs 953.8 ± 6.5 EUR; P = .0002). Similar results were observed when including the costs of patient production loss. Conclusions: As a competitive time procedure, the in situ off‐line method proved to be cost‐efficient by effectively offering similar patient treatment per year compared with the on‐line procedure.